Biblische Bezüge in Moby-Dick: Teil 2: Der weiße Wal als biblischer Leviathan und die Jona-Predigt von Father Mapple - Naumann, Thomas (Die Bibel in der Kunst, 2025)
This essay is a continuation and conclusion of the study published in BiKu 2022, in which I make some forays into the biblical references in Moby-Dick. While the focus there was on Melville’s use of the Bible and the symbolism of the name Ishmael, the focus now is on Melville’s fascination with the whale, whaling and in particular the figure of the white whale Moby Dick, which Melville describes as the biblical Leviathan. It is a phantom for the narrator Ishmael and remains a fascinating but inexplicable mystery. How does the Leviathan, which is a sea dragon in the Bible, become a whale that does not appear in the original biblical texts? It was only with the European Bible translations of the early modern period that the whale entered the Bible and also the Jonah narrative. The second part deals with the references to the biblical Jonah story, the swallowing of the prophet Jonah by a large fish, about which Father Mapple gives a long sermon. An analysis of the sermon shows it to be a standard Calvinist speech, which in its basic features is closely orientated towards the Calvinist interpretation of Jonah, as can be shown by numerous examples. However, at the end it also addresses the doubts of faith that are characteristic Melville’s religiosity and faith. In the final section, Melville’s satirical treatment of the theological and natural history debates of his time, which centered on the reality of biblical miracles and the identification of the great fish from the Jonah story with a whale, is addressed